2009
DOI: 10.1002/ejoc.200801130
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Analogues of Amicetose and Rhodinose – Novel Racemic and Asymmetric Routes

Abstract: Trifluoroethanol was converted into difluorinated (racemic) analogues of amicetose and rhodinose by metallated difluoroenol acetal chemistry, protection, release of the latent difluoromethyl ketone, stereoselective reduction and ozonolysis in acidic methanol. A fortuitous separation of diastereoisomers allowed the diastereoisomeric pyranoses to be obtained cleanly. Though reductive defluorination allowed a facile entry to the route, the corresponding monofluoro sugar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The authors successfully applied the reaction to enantiomeric (–)‐99 too. Importantly, TBAF/3H 2 O is commercially available and not expensive …”
Section: Fluoride Ring Opening Of Oxiranesmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors successfully applied the reaction to enantiomeric (–)‐99 too. Importantly, TBAF/3H 2 O is commercially available and not expensive …”
Section: Fluoride Ring Opening Of Oxiranesmentioning
confidence: 99%
“…Compounds with acyl or alkoxycarbonyl protecting groups on the N‐atom favor conformation (±)‐101β or (±)‐104β because of allylic 1,3 strain, while in the case of PG = H conformation (±)‐101α or (±)‐104α is preferred (Scheme ). Initial condition screening with oxirane (±)‐101aa showed that the conditions of Percy et al were the most advantageous (Scheme ). Because purification of (±)‐101aa was problematic due to its high polarity and chemical instability, the use of Fmoc‐protected epoxypiperidines was attempted.…”
Section: Fluoride Ring Opening Of Oxiranesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The cheaper reagents TBAF/ KHF 2 were still more effective, affording the desired product in 60% yield as a single isomer (entry 6). 20 It was interesting to note that simply replacing KHF 2 with KF decreased the yield and selectivity significantly (entry 7). Further screening identified that 120 °C was the optimal temperature (entry 8), and that the molar excess of reagents could be decreased (entry 9).…”
mentioning
confidence: 99%
“…Fluorination was attempted using a range of conditions. The solvent-free reaction developed within our laboratory using commercial TBAF and KHF 2 was not sufficiently effective for this substrate [ 13 , 19 ]. The yield of the product was moderate (37%), but the purification of the product was extremely difficult due to the complex mixture of products.…”
Section: Resultsmentioning
confidence: 99%